(untitled) (Economics and region, 2020)
The modern globalized system of higher education requires higher education institutions to adapt to EU social standards. The article aims to substantiate the regional features of the development of higher education institutions in the context of social challenges. The article reveals the results of the study of the current state of the main indicators of development of higher education in Ukraine taking into account the regional aspect; analysis of the activity of higher education institutions in the field of social responsibility; priority areas for strengthening the social mission of higher education institutions. It is established that the main principles of development of higher education institutions of Ukraine in terms of gradual integration into the European community and the need to overcome social challenges are the recognition of the importance of the social mission, strengthening their social responsibility and matching the number of students to the number of teachers and institutions of higher education in the regions.